THE INFLUENCE OF INTELLECTUAL CAPITAL ON THE MARKET VALUE AND FINANCIAL PERFORMANCE OF COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Abdul Rasyid (Jurnal Multidisiplin Sahombu, 2023)
This study aims to examine the impact of Intellectual Capital on the market value and financial performance of publicly traded companies on the Indonesia Stock Exchange (BEI). "Intellectual Capital" encompasses a corporation's intangible resources, such as knowledge, expertise, invention, and reputation. The present study utilized financial data and information derived from the annual reports of manufacturing firms publicly listed on the IDX (Indonesia et al.) from 2018 to 2022. The panel regression analysis technique is employed to investigate the association between Intellectual Capital, quantified by the Value Added Intellectual Coefficient (VAIC), and the market value of a company, as indicated by the Price to Book Value (PBV) ratio, as well as its financial performance, as measured by financial ratios like Return on Assets (ROA). The study's findings indicate a positive correlation between intellectual capital (VAIC) and the Value of the Market (PBV).Furthermore, the research reveals that intellectual capital (VAIC) accounts for 23.0% of the variation in market performance (PBV). In the interim, the study's findings indicate a favorable correlation between intellectual capital (VAIC) and financial performance (ROA). Furthermore, the extent of the impact of intellectual capital (VAIC) on the company's financial performance (ROA) is measured at 31.6%.